A compact linear-cavity multi-wavelength Brillouin/thulium fiber laser in S/S+-band - Ahmad, Harith; Kamely, A.A.; Samion, Muhamad Zharif (Elsevier, 2019)
A compact Brillouin thulium-doped fluoride fiber (TDFF)multi-wavelength fiber lasers (MWFLs)operating in the S/S+ band region is proposed and demonstrated. The system is based on a linear design and utilizes two Faraday mirrors at both ends of the cavity to enable bi-directional oscillation. An 11.5 m long TDFF with an absorption rate of 0.15 dB/m at 1400 nm is used as the gain medium. A stable output laser comb with 28 Stokes lines is obtained at the maximum pump power of 250 mW at the wavelength of 1488 nm. The multi-wavelength Brillouin fiber laser can also be tuned, covering a total tuning range of 55 nm from 1460 nm to 1515 nm. The proposed system is highly stable, and would have significant practical applications. © 2019